2012
DOI: 10.1152/ajpheart.00637.2011
|View full text |Cite
|
Sign up to set email alerts
|

The heart-specific NH2-terminal extension regulates the molecular conformation and function of cardiac troponin I

Abstract: Akhter S, Zhang Z, Jin JP. The heart-specific NH2-terminal extension regulates the molecular conformation and function of cardiac troponin I. Am J Physiol Heart Circ Physiol 302: H923-H933, 2012. First published December 2, 2011; doi:10.1152/ajpheart.00637.2011.-In addition to the core structure conserved in all troponin I isoforms, cardiac troponin I (cTnI) has an ϳ30 amino acids NH 2-terminal extension. This peptide segment is a heart-specific regulatory structure containing two Ser residues that are substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 48 publications
1
25
0
2
Order By: Relevance
“…This specificity is present in early developmental stages in the embryo, where cardiac troponins are only expressed in beating heart tissue (Filipczyk et al 2007) and are mediated by a number of mechanisms, including specific promoters for cardiac troponin (Harlan et al 2008) and an amino acid sequence different from other troponin proteins (Akhter et al 2012). However, later in life, the troponin complex is prevalent in other tissues as well, and there is evidence suggesting that under certain conditions, genes encoding the cardiac troponin complex (type c) can undergo activation and be expressed even in the brain (Lyckman et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This specificity is present in early developmental stages in the embryo, where cardiac troponins are only expressed in beating heart tissue (Filipczyk et al 2007) and are mediated by a number of mechanisms, including specific promoters for cardiac troponin (Harlan et al 2008) and an amino acid sequence different from other troponin proteins (Akhter et al 2012). However, later in life, the troponin complex is prevalent in other tissues as well, and there is evidence suggesting that under certain conditions, genes encoding the cardiac troponin complex (type c) can undergo activation and be expressed even in the brain (Lyckman et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While the N-terminal extension of cTnI does not have definitive interaction with other known myofilament proteins, it plays a role in modulating the conformation of other regions of the cTnI molecule (Akhter et al, 2012). …”
Section: Structure-function Relationship Of Tni Isoformsmentioning
confidence: 99%
“…The N-terminal extension contains the key PKA phosphorylation sites and plays a role in modulating the overall molecular conformation and function of cTnI (Akhter et al, 2012). Different from the C-terminal truncation, a selective removal of the N-terminal extension of cTnI through restrictive proteolysis occurs as a regulatory mechanism in cardiac adaptation in physiological and pathological stress conditions.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…cTnI also contains a calcium dependent regulatory region and a coiled-coil region (the I–T arm) that interacts with TnT and transmits calcium signals in the troponin complex 1215 . Recent studies have suggested that the N-terminal extension of cTnI regulates the function of cTnI through long range conformational effect on the I–T interface 15, 16 .…”
mentioning
confidence: 99%